Adsorption of vancomycin on Amberlite XAD-16 in a packed bed column - Borin, B. (Array, 2009)
Summary: Vancomycin is a glycopeptide used in the prophylaxis and treatment of bacterial infections. It is obtained with fermentation of bacteria called Amycolatopsis orientalis. After fermentation, it is purified of coloured additions and inorganic salts by adsorption to a polymeric adsorbent Amberlite XAD-16. In this work, equilibrium adsorption studies to determine the adsorption capacity were done first. The experimental data fitted best with Langmuir isotherm. Maximum capacity was q0 = 53.76 kg m–3 resin at pH 7. Next, adsorption was studied in a laboratory packed bed adsorption column. A simple mathematical model taking into account axial dispersion was applied to describe the dynamics of the process with breakthrough curves. Experimental and predicted results were compared, and some parametric sensitivity analysis was made to better understand the process for the purpose of scale up